Open Reduction and Internal Fixation Versus Hemiarthroplasty in the Management of Proximal Humerus Fractures. (June 2014) - Thorsness, Robert; Iannuzzi, James; Noyes, Katia; Kates, Stephen; Voloshin, Ilya
Objectives: The purpose of this study was to use a nationally representative database to determine the differences in 30-day outcomes based on procedure type for management of proximal humerus fractures including complications, readmission, operative time, and length of stay. Further, we sought to determine patient characteristics and perioperative factors associated with poor outcomes. Design/Setting: This was a retrospective study of the National Surgical Quality Improvement Program (NSQIP) database. The NSQIP comprises a clinical database with systematic patient tracking at multiple hospitals across the United States. Patients: A total of 413 patients with proximal humerus fractures managed surgically were included. Intervention: Of 413 patients, 330 underwent open reduction and internal fixation (ORIF) and 83 underwent hemiarthroplasty. Main Outcomes/Measurements: The primary end points included major and minor complications, operative time, rate of return to the operating room, and length of stay. Results: Compared to the hemiarthroplasty cohort, patients in the ORIF cohort were significantly younger (64.2; 17-90 and 69.3; 20-90, respectively, P = .007) and were significantly less likely to be of functionally dependent status (17.5% and 27.7%, P = .036). Compared to the hemiarthroplasty cohort, the ORIF cohort demonstrated fewer postoperative bleeding complications (2.4% and 8.4%, respectively, P = .016) and shorter operative times (115 vs 131 minutes, P = .017). There were no significant differences between the groups with respect to complications, reoperation rates, or length of hospital stay. On multivariable analysis, hemiarthroplasty demonstrated increased risk of postoperative bleeding compared to ORIF (odds ratio = 7.06, confidence interval: 2.06-24.24; P = .002) as well as increased operative time ( P = .01). Conclusions: Patients who undergo hemiarthroplasty for management of proximal humerus fractures are significantly older and often functionally dependent. When compared to ORIF, hemiarthroplasty is associated with longer operative times and greater risk of bleeding complications.